Picrasane quassinoids from Picrasma javanica - Koike, Kazuo; Yokoh, Mika; Furukawa, Mika; Ishii, Satoko; Ohmoto, Taichi (Phytochemistry (Oxford), 1995)
Three new picrasane quassinoids were isolated from the bark of Picrasma javanica. Their structures were established using spectroscopic data and X-ray analysis. The absolute stereochemistry of their structure was determined by a modified form of Mosher's method and CD spectra.